The Impact of Fashion x Culinary Co-Branding on Customer Evaluation - Maharani, Khansa; Aprilianty, Fitri (Journal Integration of Management Studies, 2023)
Existing literature has extensively explored the influence of co-branding on customer evaluation, particularly concerning variables such as brand personality, product fit, brand fit, brand attachment, and brand awareness. However, a research gap in implementing co-branding exists in the specific context of fashion x culinary. Consequently, this study aims to investigate the impact of these variables on customer evaluation of fashion x culinary co-branding products. To achieve this, a quantitative research methodology is employed, involving collecting data from 498 cases, which is subsequently analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The findings reveal a significant influence of fashion x culinary co-branding on customer evaluation. Notably, the indirect effect of perceived co-brand personality on customer evaluation, mediated by brand awareness, emerges as the most influential factor. These findings contribute to the existing body of research on co-branding and brand alliances by offering new insights and recommendations that have the potential to enhance industry practices.